Development of an in-house dual RT-qPCR assay for detecting SFTSV and Hantaan virus simultaneously - Xiaoyu Xue; Youde Liu; Chuan Song; Tingting Liu; Zishuai Liu; Wenjing Niu; Zhouling Jiang; Yanli Xu; Yuanyuan Zhang; Ling Lin; Zhihai Chen (Biosafety and Health)
Given the overlapping endemic regions and clinical similarities between severe fever with thrombocytopenia syndrome (SFTS) and hemorrhagic fever with renal syndrome (HFRS), we developed a dual real‐time fluorescence‐based reverse transcription quantitative polymerase chain reaction (RT-qPCR) method. Recombinant plasmids and synthetic ribonucleic acid (RNA) were constructed to evaluate the specificity, sensitivity and reproducibility of the assay. Additionally, we assessed the specificity of the assay using samples from three distinct groups: individuals with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (n = 10), influenza A-positive individuals (n = 10), and healthy controls. Receiver operating characteristic (ROC) curves were used to assess diagnostic accuracy, while the Kappa coefficient and linear regression analysis were employed to evaluate clinical applicability. Our method exhibited specificity for both SFTSV and Hantaan virus detection, with detection limits of 333 and 1,022 copies/mL using plasmids, and 1,247 and 898 copies/mL using synthetic RNA, respectively. We evaluated 100 clinical samples from each of SFTS and HFRS. The Kappa coefficients for both diseases were 0.96. The areas under the ROC curves were 0.991 (P < 0.001) and 0.989 (P < 0.001), respectively. The linear regression equations were as follows: log (y) = 0.19 + 0.99 log (x) (R2 = 0.95) for SFTS virus, and log (y) = 0.01 + 0.65 log (x) (R2 = 0.92) for Hantaan virus. We established an in-house RT-qPCR method for the rapid quantification of both pathogens, making it an ideal tool for early clinical differentiation.